Second: race and guns in a fatally unequal america - Anderson, Carol (Bloomsbury Publishing, 2021)
Historian Carol Anderson powerfully illuminates the history and impact of the Second Amendment, how it was designed, and how it has consistently been constructed to keep African Americans powerless and vulnerable. Through compelling historical narrative merging into the unfolding events of today, Anderson's penetrating investigation shows that the Second Amendment is not about guns but about anti-Blackness, shedding shocking new light on another dimension of racism in America. Print run 250,000